Carbon dynamics of fruit and vegetable wastes and biodegradable municipal waste compost-amended oxisol - Musa, Aishatu Mala; Ishak, Che Fauziah; Md. Jaafar, Noraini; Karam Singh, Daljit Singh (Multidisciplinary Digital Publishing Institute, 2021)
Recycling of wastes via composting is advocated as a means to reduce environmental hazards due to the dumping of wastes. Composting also creates a vital source of organic matter that is important in nutrient and soil moisture retention, soil fertility preservation and improving the physical and chemical properties of soils. This study was conducted to evaluate the short-term effects of four compost amendments in an Oxisol on carbon dynamics (carbon dioxide evolution and carbon transformation). The composts were prepared in 3:1 and 1:2 of fruit and vegetable waste (FVW) to biodegradable municipal waste (BMW) with and without indigenous microorganisms (IMO) (3:1 +IMO, 1:2 +IMO, 3:1 −IMO, 1:2 −IMO). Soil incubation studies were carried out for 35 days at three compost application rates of 0, 5 and 10 Mg ha−1, with measurements done including the CO2 evolution, dehydrogenase enzyme (DHA) assay and compost Fourier transform infrared (FTIR) spectroscopy spectral analysis. At 10 Mg ha−1 compost application rate, increased soil respiration rate was obtained at 3:1 +IMO compost, mostly due to increased labile organic matter and higher amount of FVW in the compost mixture, which stimulated soil microorganisms and/or their activities reflected by increased evolution of CO2 in the process of decomposition of the added composts in the compost-amended soils. The DHA activity increased with compost application rates, and significantly, the highest DHA activity was recorded at 3:1 +IMO compost applied at 10 Mg ha−1 soil at 1.38 triphenylformazan (TPF)/g dry soil/24 h. The compost FTIR spectral analysis showed transformations that occurred due to the composting that was carried out. A broadband between 3279–3347 cm wavelength in the FTIR spectroscopy indicated the presence of carboxylic and hydroxyl functional groups because of carbon transformation that occurred in the composts.